Ketrampilan Bahasa Jepang Bagi Karyawan PT. Java Agritech Semarang - Muryati, Sri; Astuti, Bekti Setio (Universitas Diponegoro, 2023)
This study aims to determine the Japanese language skills needed by employees of PT. Java PT. Java Agritech Semarang. This research is the basis for Japanese language training activities that will be carried out as a form of cooperation between PT. Java Agritech Semarang and Japanese Language Study Program, so that training can run effectively and efficiently. Needs analysis is important to be carried out so that teachers can determine the right material, teaching methods, and references and can answer employee needs. The population of this study were employees of PT JAT Semarang not Japanese language professionals. Survey, questionnaire and interview methods are used to obtain data on employee needs for Japanese which refers to Target Needs and Learning Needs. . The results showed that 92.8% of respondents needed mastery of Japanese. Specifically, the mastery needed is work-related vocabulary, basic grammar and expressions in communicating. This aspect has an important role in four language skills, namely listening, reading, speaking, and writing. Of the four skills, respondents sequentially need speaking skills, listening skills, writing and reading. Speaking and listening skills include the ability to convey and identify greetings, name and point objects, ask and understand questions and simple explanations in Japanese. Reading and writing skills are only needed by 24% of respondents, to read and write emails in Japanese. <a href=